FLOWERING LOCUS C (FLC) regulates development pathways throughout the life cycle of arabidopsis. - Deng, Weiwei; Ying, H.; Helliwell, C.; Taylor, J.; Peacock, W.; Dennis, E. (PNAS, 2011)
FLOWERING LOCUS C (FLC) has a key role in the timing of the initiation of flowering in Arabidopsis. FLC binds and represses two genes that promote flowering, FT and SOC1. We show that FLC binds to many other genes, indicating that it has regulatory roles other than the repression of flowering. We identified 505 FLC binding sites, mostly located in the promoter regions of genes and containing at least one CArG box, the motif known to be associated with MADS-box proteins such as FLC. We examined 40 of the target genes, and 20 showed increased transcript levels in an flc mutant compared with the wild type. Five genes showed decreased expression in the mutant, indicating that FLC binding can result in either transcriptional repression or activation. The genes we identified as FLC targets are involved in developmental pathways throughout the life history of the plant, many of which are associated with reproductive development. FLC is also involved in vegetative development, as evidenced by its binding to SPL15, delaying the progression from juvenile to adult phase. Some of the FLC target genes are also bound by two other MADS-box proteins, AP1 and SEP3, suggesting that MADS-box genes may operate in a network of control at different stages of the life cycle, many ultimately contributing to the development of the reproductive phase of the plant.